HUBUNGAN ANTARA MOTIVASI BERPRESTASI DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA GURU DI MAS NURUL IMAN SUKARAMAI KECAMATAN BILAH BARAT KABUPATEN LABUHANBATU - Bascanti Ritonga (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This study aims to determine 1) The relationship of achievement motivation with teacher work productivity in MAS Nurul Iman Sukaramai District West Bilah Labuhanbatu District. 2) Relationship of job satisfaction with teacher work productivity in MAS Nurul Iman Sukarmai District West Bilah Labuhanbatu District. 3) Relationship of motivation and work satisfaction with teacher work productivity in MAS Nurul Iman Sukarami District West Bilah Labuhanbatu District. This research uses quantitative research type. With a population of 30 and a sample of 28 teachers. The data collection techniques with observation and dispute of the questionnaire. The technique used in analyzing data is by using the technique of Double Correlation. The findings of this study are as follows: there is a positive relationship of achievement motivation and job satisfaction on teacher work productivity in MAS Nurul Iman Sukaramai subdistrict West Bar Labuhanbatu regency. This is proven by the calculation obtained that the value of rhitung = 0.850 at 95% level or alpha 5% with dk = N - 2 (28-2) is 0.374 or rhitung (0.850) ˃ rtabel (0.374). The result of double correlation can be seen from R2 equal to 0,542 with interpretation of moderate level of relationship. Means that the magnitude of the relationship between achievement motivation and job satisfaction with work productivity is 54.2% and 46.8% influenced by other factors. In this research can be know that 1) the relationship between achievement motivation with teacher work productivity in MAS Nurul Iman Sukaramai District West Bilah Labuhanbatu district with value r count 0,402. 2) the relationship between job satisfaction with the work of teachers MAS Nurul Iman Sukarmai District West Bilah Labuhanbatu district with a value of r calculate 0,542. 3) the relationship between achievement motivation and job satisfaction on teacher work productivity in MAS Nurul Iman Sukaramai District West Bilah Labuhanbatu district with R value count of 0.850.Keywords: Achievement Motivation, Job Satisfaction and Work Productivity.